Ba-enhanced Dwarf and Subgiant Stars in the LAMOST Galactic Surveys - Meng Zhang; Maosheng Xiang; Hua-Wei Zhang; Yuan-Sen Ting; Ya-Qian Wu; Xiao-Wei Liu (The Astrophysical Journal, 2023)
Ba-enhanced stars are interesting probes of stellar astrophysics and Galactic formation history. In this work, we investigate the chemistry and kinematics of a large sample of Ba-enhanced ([Ba/Fe]>1.0) dwarf and subgiant stars with 5000 < T _eff < 6700 K from LAMOST. We find that both stellar internal evolution processes and external mass exchange due to binary evolution are responsible for the origins of the Ba enhancement of our sample stars. About one third of them exhibit C and N enhancement and an ultraviolet brightness excess, indicating they are products of binary evolution. The remaining Ba-enhanced stars with normal C and N abundances are mostly warm stars with T _eff > 6000 K. They are likely the consequences of stellar internal element transport processes, but they show very different element patterns to hotter Am/Fm stars. Our results reveal a substantially lack of high-[ α /Fe], Ba-enhanced stars in the [Fe/H]–[ α /Fe] plane, which we dub as a “high-[α/Fe] desert”. We suggest it is due to a lower efficiency for producing Ba-enhanced stars by low-mass asymptotic giant branch progenitors in binary systems. Our results call for detailed modeling of these Ba-enhanced stellar peculiarities, in the context of both stellar internal element transport and external mass accretion.